Recent advances in thermochemical conversion of biomass - Pandey, Ashok; Bhaskar, Thallada; Stocker, Michael (Chemist); Sukumaran, Rajeev (Amsterdam : Elsevier, 2015)
Provides information on the most advanced and innovative biohydrogen technology Useful as reference book Provides examples on large scales and commercial applications of biohydrogen processes Useful for researchers intending to study sacle-up Provides information on integration of process and technology on biohydrogen Useful for researchers and industry A book designed as a text book not merely a collection of research articles Useful as text book for graduate students and reference book for researchers.
3.3.3. Thermal Decomposition Products as Measured by Thermogravimetry/Mass spectrometry3.3.4. Reaction Kinetic Modeling Using Thermogravimetric Data; 3.4. Analytical Pyrolysis; 3.4.1. Pyrolysis Techniques; 3.4.2. Pyrolysis of Macromolecular Biomass Constituents; 3.4.3. Pyrolysis of Whole Biomass Samples; 3.5. Reaction Mechanisms of the Thermal Decomposition; 3.5.1. Cellulose Decomposition; 3.5.2. Hemicellulose Decomposition; 3.5.3. Lignin Decomposition; 3.5.4. Mechanisms of Biomass Pyrolysis; 3.6. Effect of Inorganic Materials on the Decomposition Mechanism
Includes bibliographical references at the end of each chapters and index.
CIP data; item not viewed.
Elsevier
Keywords: Biomass conversion; Biomass energy; Thermochemistry; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Biomass conversion; Biomass energy; Thermochemistry; Electronic books; Electronic books